Process Approach in the Teaching of Writing for Undergraduate EFL Students - Yogi Setyawan; N. K. Arie Suwastini; Ni Made Ratminingsih (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2020)
Background: This research aimed to investigate the implementation of a process approach for EFL undergraduate students in a private university in Bali. Methodology: The present study involved one lecturer and thirty students enrolled in Paragraph Writing Class. Observations were conducted in twenty-eight meetings of the total meetings to reveal - that strategies of process approach were implemented in each of the stages of writing, namely, prewriting, drafting, editing, revising and, publishing. Findings: The lecturer implemented all nine strategies where seven strategies were optimally conducted and all ten strategies were implemented by the students, where nine strategies were optimally conducted during the editing stage. In the publishing operation, the instructor implemented three of three strategies, and students implemented three of three strategies. Conclusion: Strategies of process approach were implemented by the lecturer and the students during the Paragraph Writing Course. It is implied that in an implementation of a process approach in a writing class, the lecturer and the students need to work together in most of the stages to create a good writing process.